(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
This issue investigates the Italian documentary film with particular attention to the contemporary production. In particular, it maps some of the main influences that have characterized and that characterize today the Italian documentary, analysing the films of Michelangelo Frammartino, Alina Marazzi, Sabina Guzzanti and Silvio Soldini, among others.